Influence of pulverized coal deposition on proppant-filled fracture conductivity - ZHOU Yang (Meikuang Anquan, 2022)
In order to study the influence mechanism of pulverized coal deposition produced in the process of hydraulic fracturing on the conductivity of proppant-filled fracture and effectively optimize the drainage mechanism of coalbed methane wells, the proppant-filled fracture multiphase flow experimental platform is used to formulate the corresponding experimental scheme. The damage of proppant filling fracture conductivity caused by pulverized coal produced in the drainage and production of coalbed methane wells is experimentally studied. The results show that the greater the mass fraction of suspended pulverized coal, the later the water outlet time of proppant-filled fracture, and the greater the pressure difference at the water outlet point; with the increase of suspended pulverized coal mass fraction, the pulverized coal deposition in the fracture shows a linear growth trend. The pulverized coal deposition first increases sharply to the maximum value and then decreases slowly. The permeability and conductivity of proppant filled fracture show a downward trend.